Measuring Population and Housing in Eastern Europe, Caucasus and Central Asia - United Nations (United Nations, 2017)
The population and housing census provides, at regular intervals, information on the number and characteristics of the population of a Country, and on its housing stock. It is an essential source of information for small-area, national, regional and International planning and development. This publication reviews the practices followed by countries in Eastern Europe, Caucasus and Central Asia in the population and housing censuses of the 2010 round (taken between 2009 and 2014). The aim is to compare the different approaches and practices adopted among these countries as well as with those in other countries in Europe and North America. and to assess the compliance with the